Monetary policy response on exchange rate volatility in Indonesia - Ferry Syarifuddin; Noer Azam Achsani; Dedi Budiman Hakim; Toni Bakhtiar (Journal of Contemporary Economic and Business Issues, 2014)
High fluctuation of exchange rate in short horizon is obviously making economic activity more risky as uncertainty rises. As it is not good for the economy, then there should be a systematic and measured policy to mitigate the foreign exchange fluctuations and to minimize the fluctuations, as well as to drive it to its fundamental value. In this part this research measures how persistent the exchange rate fluctuation in Indonesia is, and how are thus the central banks able to perform appropriate monetary policy, especially in determining their policy interest rate, or to make foreign exchange intervention to stabilize the exchange rate. In this study, USD/IDR volatility is investigated using TGARCH approach. The result reveals that, USD/IDR volatility in Indonesia is obviously persistent. This study also presents the outcomes of effectiveness of policy response by the Central Bank. Foreign-exchange sale interventions by the Central Bank lead to a slight USD/IDR decrease. Whatever Bank of Indonesia's efforts to exert a stabilizing effect of foreign exchange interventions, the results are inconclusive.
Keywords: F31; E52; C58; 330; exchange rates; foreign-exchange intervention; GARCH